PENGARUH GAYA PENGASUHAN ORANG TUA TERHADAP PENCAPAIAN BELAJAR SISWA KELAS IV SDN 151 PEKANBARU - Pazli, Muhammad; Risna Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Parents play a crucial role in determining their child's academic success at school. Implementing appropriate parenting styles will help children develop optimally, both academically and character-wise. Parents are not only responsible for meeting their child's physical needs, but also for providing emotional support, motivation, and consistent tutoring. By creating a comfortable, safe, and caring home environment, children will feel more confident in facing learning challenges. Furthermore, good communication between parents and children can help them understand their child's learning difficulties. Parents also need to collaborate with teachers to monitor their child's academic progress. Through positive parenting styles, children will develop discipline, responsibility, and a strong enthusiasm for learning, thereby maximizing their academic performance. This study aims to analyze the influence of various parenting styles including authoritarian, permissive, and democratic on the learning outcomes of fourth-grade students at SDN 151 Pekanbaru. A quantitative approach with an ex post facto design was used in this study. The research sample consisted of 54 students selected as respondents. Data were collected through questionnaires and documentation studies, while data analysis was conducted using multiple linear regression. The results of the study indicate that: (1) authoritarian parenting styles have a partial significant influence on learning outcomes, (2) permissive parenting styles do not show a partial significant influence, (3) democratic parenting styles have a partial significant influence, and (4) all three parenting styles simultaneously influence the learning outcomes of fourth-grade students at SDN 151 Pekanbaru. Based on these findings, it is recommended that parents adjust the implementation of the three parenting styles according to the child's psychological conditions and needs.